Development of Learning Module Building Technology using Model Sidek - Yassin, Sarafatimah; Ariffin, Arihasnida; Rubani, Siti Nur Kamariah; Hamzah, Norhasyimah; Zakaria, Normah (Research and Innovation in Technical and Vocational Education and Training, 2022)
Building Technology 1 is a course offered to students of this program. This study aimed to develop and test the usability of learning module of Building Technology 1 in terms of design and content of the module. The research design of this study is the product development design. Based on this research form, there are three phases in module development, Phase 1: Need Analysis Phase, Phase ll: Design and Development Phase and Phase lll: Evaluation Phase. In the need analysis phase, the preliminary analysis questionnaire was used to identify the needs of module development. The design and development phase are the process of preparing a draft module based on Model Development of Sidek Module. The questionnaire instrument was validated by three experts and a pilot test had been conducted with a reliability value of design construct was 0.966 and content construct was 0.955. In the evaluation phase, the learning module validate by expert and been tested usability consist of design and content through a quantitative method. Sample of research consist of 3 experts and 27 students. The finding shows that the usability of the module was at moderate level (M=3.67). Meanwhile, the usability of the module in terms of design (M=3.89) and content (M=3.93) was at high level. Overall, in can be conclude that the design and content of learning module of Building Technology 1 that had been developed are acceptable and usable.